2016
DOI: 10.5152/tpd.2016.4792
|View full text |Cite
|
Sign up to set email alerts
|

Parasites Determined by Fecal Examination in Horses in Erzurum

Abstract: Equine animals are significantly infected with Strongylosis in the Erzurum Province, and effective parasite control measures should initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The disease is also endemic in the countries of the region. In Erzurum, Turkey, out of 76 fecal samples collected from horses, 2.6% were found infected using flotation and sedimentation methods (7). Recent emerging focus of the disease has been documented in Yasuj, southwest of Iran (8).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is also endemic in the countries of the region. In Erzurum, Turkey, out of 76 fecal samples collected from horses, 2.6% were found infected using flotation and sedimentation methods (7). Recent emerging focus of the disease has been documented in Yasuj, southwest of Iran (8).…”
Section: Introductionmentioning
confidence: 99%
“…Eimeria leuckarti was reported in 0.4% of horses in Bursa Province (Tınar et al, 1994), 3.8% of equidae in Kars Province (Arslan and Umur, 1998), 4.5% of horses in Konya Province (Uslu and Güçlü, 2007) and 1% of horses in Van Province (Erdoğan, 2019). A study conducted in Erzurum Province reported no E. leuckarti in the horses examined (Avcıoğlu et al, 2016).…”
Section: Discussionmentioning
confidence: 90%